Abundância e sazonalidade de dípteros (Insecta) em granja aviária da região nordeste do Estado de São Paulo, Brasil - Lopes, Welber Daniel Z. [UNESP]; Costa, Fabio H. da; Lopes, Wilton Car-Los Z.; Balieiro, Julio Cesar de C.; Soares, Vando E.; Prado, Angelo P. do (Brazilian Coll Veterinary Parasitology, 2008)
Modem production systems accommodate broody hens in high densities, leading to the accumulation of excrement under the cages. This substrate is excellent for the development of sinantropic flies. Thus, the accomplishment of surveys in these places becomes essential, in order to plan better strategies of control. The present work aimed at studying the entornofauna and the seasonality of the species of dipterous present in the Crisdan poultry house located in the Municipality of Sao Joao da Boa Vista, the State of São Paulo, Brazil. In the period of January of 2001 to December of 2002, 1,012,595 flies were captured using the "jug-trap". The species were identified: Drosophi-la repleta (Wollaston, 1858), Musca domestica (Linnaeus, 1758), Ophyra spp., Hennetria illucens (Linnaeus, 1758), Fannia canicularis (Linnaeus, 1761), Chrysomya megacephala (Fabricius, 1794), and Sepsidae. More frequently D. repleta and M. domestica had added 99.47% of the dipterous. Increased rainfall and the collection months influenced the sampling of dipterous (P < 0.05). Drosophila repleta was the most abundant species, representing 91% of all captured flies. However, this diptera did not develop at the surveyed site since immatures were not captured therein.

Nos sistemas modernos de produção de ovos, as aves poedeiras são alojadas em altas densidades, acumulando esterco sob as gaiolas. Esse substrato é excelente para o desenvolvimento de moscas sinantrópicas. Sendo assim, se torna essencial a realização de levantamentos de moscas nesses locais, a fim de se planejar uma melhor estratégia de controle. O presente trabalho teve como objetivo estudar a entomofauna e a sazonalidade das espécies de dípteros da granja Crisdan, em São João da Boa Vista, São Paulo, Brasil. No período de janeiro de 2001 a dezembro de 2002 foram capturados 1.012.595 exemplares utilizando-se armadilha "jug-trap". As espécies identificadas foram: Drosophila repleta (Wollaston, 1858), Musca domestica (Linnaeus, 1758), Ophyra spp., Hermetria illucens (Linnaeus, 1758), Fannia canicularis (Linnaeus, 1761), Chrysomya megacephala (Fabricius, 1794) e Sepsidae. Com maior freqüência D. repleta e M. domestica representaram 99,47% dos dípteros capturados. A elevação dos índices pluviométricos em alguns meses dos anos influenciaram a amostragem de dípteros (P<0,05). D. repleta representou cerca de 91% de toda população. Entretanto, este díptero provavelmente não estava se desenvolvendo no local, já que estágios imaturos não foram capturados.
Abundance and seasonality of Diptera (Insecta) in a poultry house in the northeast region of the state of São Paulo, Brazil
Keywords: Arthropod; Drosophila repleta; Flies; Poultry house